The Effect of Leadership and Work Discipline on Teacher Performance - Wulandari, Melia; Fitria, Happy; Wahidy, Achmad (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to determine the effect of leadership and work discipline on the performance of public elementary school teachers in Cluster I, Rambutan District, Banyuasin Regency. This type of research is quantitative. The sample in the study was 55 respondents with data collection techniques in the form of a questionnaire (questionnaire). The results showed that: 1) there is a significant influence of leadership on teacher performance, 2) there is a significant effect of work discipline on teacher performance, 3) there is a significant influence between leadership and work discipline on teacher performance.